Tsoukatos, Evangelos - (:unkn) unknown (My University, 2026)
Dr Evangelos Tsoukatos teaches Management at the Technological Educational Institute of Crete, Greece and is adjunct faculty at the University of Nicosia, Cyprus the University of Gloucestershire, UK and the Hellenic Open University. He earned a B.Sc. in Mathematics from the ‘Aristotelion” University of Thessaloniki, Greece, a Postgraduate Diploma and M.Sc. in Operational Research from Lancaster University Management School (LUMS), UK, where from he also earned his Ph.D. in Management. Prior to joining academia he had extensive experience as consultant and in senior management positions. He won the “Brian Kingsman prize for best doctoral researcher” and shares with Evmorfia Mastrojianni the 2011 Emerald best paper award.. He is Associate Editor of the EuroMed Journal of Business (EMJB) and editorial board member in a number of international scholarly journals. He won the, 2015 Emerald Literati Network Awards for Excellence, Outstanding Reviewer for the International Journal of Organizational Analysis Award. His research interests are in Services Management, Quality Management, Cross-Cultural Management and Entrepreneurship. Dr Evangelos Tsoukatos has been involved, over the years, in various national and international research and educational projects. He holds the position of Vice President – Operations and Development at the EuroMed Research Business Institute. He authored and edited books and journal special issues and has heavily published internationally in scholarly journals and presented in academic conferences. For his published research, Dr Tsoukatos has gained wide recognition from his peers. Further info about Dr Tsoukatos is available at http://teicrete.academia.edu/EvangelosTsoukatos